Reconstrução do clima no nordeste brasileiro. Secas e enchentes do século XIX - Osvaldo Girão (Finisterra - Revista Portuguesa de Geografia, 2012)
Climate reconstruction in northe astern Brazil. Floods and droughts in the 19th ce ntury. The temporal evolution of the natural environment dynamics, and its consequences for societies affected by natural phenomena, has been included in the syllabus of Historical Climatology since the Annales School. This article assesses the evolution of such studies concerning the Brazilian instrumental series and the evaluation of extreme weather events (droughts and floods), as well as their impact on the socio-economic dynamics of the nineteenth century northeastern Brazil.